PELATIHAN PENCATATAN KEUANGAN DAN TEKNIK PEMASARAN DIGITAL PADA USAHA PENEK BAPAK SUDA DI DESA SIDAN, KECAMATAN GIANYAR, KABUPATEN GIANYAR - Ni Nyoman Adityarini Abiyoga Vena Swara; Ni Luh Adisti Abiyoga Wulandari; Ni Komang Sumadi; Luh Nik Oktarini (UNHI Press, 2020)
Covid19 pandemic has caued a lot of disruption in every community activity, especially work. Almost all people carry out activities at home or work from home. However, not all companies implement this, because this pandemic has also made many companies temporarily close their businesses until the Covid19 pandemic ends. This happens in almost all over the world, including in Indonesia. D Indonesia itself, the impact of this pandemic has greatly disrupted the tourism sector on the Island of the Gods. The Island of the Gods, whose main business is the tourism sector, has made many people lose their jobs and are forced to look for alternative businesses that can generate money to meet their daily needs. The penek rice business, which is a business that is always sought after because it is a ceremonial necessity for the Hindu religious community in Bali, is one of them. Mr. Suda's penek rice business has only been running for four months and is carried out at his residence in Sidan Village, Gianyar District, Gianyar Regency. This business can be said to have great benefits, but because of the lack of knowledge, there are still obstacles in calculating the profits obtained. Therefore, to help this business we provide training on financial recording and digital marketing techniques so that later this business can be more developed and in the future it is hoped that it can also absorb a lot of workforce. This of course aims to improve the welfare of the community in the presence of the Covid19 pandemic.